2014
DOI: 10.15171/ijhpm.2015.06
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate control of diabetes and metabolic indices among diabetic patients: A population based study from the Kerman Coronary Artery Disease Risk Study (KERCADRS)

Abstract: Background: The goal of diabetes control should be feasible in order to minimize the risk of its adverse events and to reduce its burden and cost on patients. The current study aimed to assess the status of glycemic control in male and female patients with Type 2 Diabetes Mellitus (T2DM) in Kerman, Iran. Methods: In the present study, 500 T2DM (300 women and 200 men) from the Kerman Coronary Artery Disease Risk Study (KERCADRS), a population-based study from 2009 to 2011, were selected. Patients were >18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 42 publications
6
21
2
Order By: Relevance
“…As might be expected, having a time since diagnosis of T2D of at least 10 years compared with 0 to 5 years was also strongly correlated with poor glycaemic control. This finding is consistent with other observational studies that have demonstrated a positive relationship between disease duration and poor glycaemic control . The trend is likely to reflect the continual decline in β‐cell function that is characteristic of T2D.…”
Section: Discussionsupporting
confidence: 91%
“…As might be expected, having a time since diagnosis of T2D of at least 10 years compared with 0 to 5 years was also strongly correlated with poor glycaemic control. This finding is consistent with other observational studies that have demonstrated a positive relationship between disease duration and poor glycaemic control . The trend is likely to reflect the continual decline in β‐cell function that is characteristic of T2D.…”
Section: Discussionsupporting
confidence: 91%
“…Good glycaemic control (HbA1c < 7%) was observed in approximately one-thirds of the diabetic rural and urban population in our study which is in accordance with the study by Unnikrishnan R [17]. Another study [14]reported the mean level of HbA1c in total subjects as 8.56 ± 4.72% (mean 7.80%) in which only 31.66% of men and 26% of women had controlled level of HbA1c (<7%). Our study showed a lower mean HbA1c of 8.2±1.64, and a higher percentage 34.9% of males and 31.6% of the female diabetics having an HbA1c <7%.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that the mean BMI of the Asian subjects was lower compared to that of patients from other ethnic backgrounds and the risk of type 2 diabetes starts at a lower BMI for Asians than other ethnicities. The mean BMI of the subjects in other studies was 26 kg/m 2 [13] and in another study BMI in female diabetics was 28.60 ± 4.91 and 26.47 ± 4.68 in male diabetics [14]. Our study is in agreement with this study with BMI being 28.58±5.02 and 26.64±4.87 in female and male diabetics.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other studies suggest a gender disparity of 10-15%, women being the dominant group [65,66]. The under-recognition of the risk of hyperglycemia in women with T2DM may lead to less effective prevention, clinical care, and outcomes.…”
Section: Discussionmentioning
confidence: 99%